Elimination of the Category of Masculinity and Fatherhood in the Theory and Practice of Education - Witold Starnawski (Nicolaus Copernicus University in Toruń, 2012)
One of the most important sources of the modern crisis of education is the absence of the category of fatherhood - the foundations of that crisis lie in the field of philosophy, culture and civilization. Fatherhood can be understood in two ways: "from the bottom" and "from the top". The first one is based on a biological concept of a man (a male). The second one refers to a spiritual (personal) concept of fatherhood - it is the form of love and its ideal example is God's fatherhood. The paternal model of pedagogy includes: 1) power (especially self-control), 2) courage, 3) respect for principles (honour), 4) responsibility for others (for the family), 5) selflessness, 6) objectivity. Problems related to fatherhood require good metaphysics and anthropology - the appropriate basis for considering these issues can be found in "Theology of the body" by John Paul II.